2017
DOI: 10.1083/jcb.201607031
|View full text |Cite
|
Sign up to set email alerts
|

TOPBP1Dpb11 plays a conserved role in homologous recombination DNA repair through the coordinated recruitment of 53BP1Rad9

Abstract: The scaffold protein TOPBP1Dpb11 has been implicated in homologous recombination DNA repair, but its function and mechanism of action remain unclear. Liu et al. define a conserved role for TOPBP1Dpb11 in recombination control through regulated, opposing interactions with pro- and anti-resection factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 77 publications
3
87
0
Order By: Relevance
“…The interaction between Slx4 and Dpb11 is strongly induced by Mec1-dependent Slx4 phosphorylation in response to MMS treatment [70,72]. The dependency on Rad9 for survival of HU-treated mec1-100 cells is likely not due to decreased Slx4 phosphorylation, A B C Figure 6.…”
Section: Embo Reportsmentioning
confidence: 97%
“…The interaction between Slx4 and Dpb11 is strongly induced by Mec1-dependent Slx4 phosphorylation in response to MMS treatment [70,72]. The dependency on Rad9 for survival of HU-treated mec1-100 cells is likely not due to decreased Slx4 phosphorylation, A B C Figure 6.…”
Section: Embo Reportsmentioning
confidence: 97%
“…However, 53BP1 appears to regulate activation of the checkpoint through a more complex mechanism, as the physical interaction between CHK2 and 53BP1 rapidly decreases upon IR radiation rather than becoming stabilized (Wang et al , ), in contrast to the Rad9–Rad53 interaction, which increases after DNA damage in budding yeast. Both 53BP1 and Rad9 play a key role in the control of DNA end resection, highlighting the connection and coordination between checkpoint signaling and the regulation of DNA repair (discussed in detail later in this review; Lazzaro et al , ; Bunting et al , ; Chapman et al , ; Zimmermann et al , ; Ferrari et al , ; Liu et al , ). In both cases, phosphorylation of Rad9/53BP1 by Mec1 or Tel1 in yeast or ATM in humans is essential for suppressing DNA end resection (Bothmer et al , ; Ferrari et al , ), and it is possible that 53BP1's function in preventing resection contributes to the stabilization of ATM at breaks, which may indirectly promote ATM–CHK2 signaling.…”
Section: Introductionmentioning
confidence: 97%
“…Recent work from our laboratory has revealed that phosphorylation of these proteins correlates with the ability of cells to suppress GCRs, suggesting that proper control of HR repair is essential for preventing chromosomal rearrangements (Lanz et al , ). Phosphorylation of Slx4 by Mec1 promotes DNA end resection, the first step in the HR process (Dibitetto et al , ; Liu et al , ). Mechanistically, Mec1 phosphorylation mediates the interaction between Slx4 and Dpb11, a multi‐BRCT domain scaffold that bridges Slx4 to the 9‐1‐1 clamp loaded at 5′ recessed junctions (Ohouo et al , ; Cussiol et al , ; Fig ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rad9 53BP1 is also recruited by Dbp11 TopBP1 , forming a complex that restrains Dna2-mediated nucleolytic processing (Granata et al 2010;Pfander and Diffley 2011;Villa et al 2018). This seems conserved in human cells, where TOPBP1 stabilizes 53BP1 to the sites of damage to inhibit DSB resection (Cescutti et al 2010;Zimmermann et al 2013;Chapman et al 2013;Ochs et al 2016;Liu et al 2017) and in S. pombe where the 53BP1 orthologue, Crb2, specifically inhibits the RecQ-helicase-dependent long-range resection pathway (Leland et al 2018). In both S. pombe and mammalian cells, another resection inhibitor, Rev7 seems to be at play although its mechanism of action is unknown (Boersma et al 2015;Xu et al 2015;Leland et al 2018).…”
Section: Resection Is Regulated At Multiple Levelsmentioning
confidence: 99%